Launching an Institutional ORCID Initiative at Florida State University - Kelly Grove; Devin Soper (Issues in Science and Technology Librarianship)
This article provides a case study about an institutional ORCID initiative at Florida State University. The authors describe how they launched the initiative with minimal resources and staff time at their disposal. The authors also describe specific strategies that can be replicated at other institutions, including identifying the right partners and most compelling use cases, and taking advantage of high-impact outreach strategies that provide the most exposure for the least time invested.